Особливості реалізації безпечної маршрутизації в інформаційно-комунікаційних системах - Лемешко, В. О.; Персіков, М. А. (ХНУРЕ, 2024)
This work is devoted to determining the features of implementing secure routing in information and communication systems. The importance of ensuring information security at all seven OSI model layers is noted. At the Network Layer, an increasingly important role in ensuring network security indicators will be assigned to routing protocols, which should adapt to the realities of today and, when forming routing metrics, take into account, along with the Quality of Service indicators, network security metrics. In addition, when configuring routers and routing protocols, it is also necessary to use existing tools to increase network security.
Keywords: безпечна маршрутизація; програмно-конфігурована мережа